Effectiveness of training programme on oil palm technologies for multipurpose extension officers of state department of horticulture, Andhra Pradesh - Prasad, M.V.; Sowjanya, P.; Sunder Rao, N.; Sarkar, Ananta; Omkar Vinay Kumar, T.M.; Rajesh, K.; Srikanth, K. (Journal of Plantation Crops, 2019)
Effectiveness of training programme on oil palm technologies for multipurpose extension officers of state department of horticulture, Andhra Pradesh